Antidepressants Preclinical, Clinical and Translational Aspects - Berend, Olivier (IntechOpen, 2019)
Major depression is a severe and prevalent brain disorder with a high disability burden, hence the push for effective treatments. Antidepressants have been around since the 1950s, and although current medications are much more effective than early ones, there is still much room for improvement. "Real" antidepressants, defined as those that "repair" or "improve" the depression-causing mechanism in the brains of depressed patients, have yet to be identified. This book presents current research on depression and antidepressants, including use of antidepressants in alcohol use disorders and pregnancy, treatment-resistant depression, and development of potential new medications.